Guidelines for prescribing opioids for chronic non-cancer pain in Korea - Kim, Eung Don (Korean J Pain, 2017)
As the treatment of chronic non-cancer pain gradually increases, clinicians have more opportunities to encounter opioid prescription. However, guidelines for prescribing opioids for chronic non-cancer pain have never been published in Korea. The present guidelines were prepared by reviewing various research data. In cases in which the data were insufficient, recommendations were presented following discussion among experts affiliated with the Opioids Research Group in the Korean Pain Society. The present guidelines may need to be continuously revised and amended as more clinical evidence is acquired.